1999
DOI: 10.1007/pl00012339
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life following Radical Surgical Treatment of Gastric Carcinoma

Abstract: Quality of life (QOL) in patients with gastric cancer who underwent total gastrectomy has so far not been studied using the EORTC QLQ-C30 (Quality of Life Core Questionnaire of the European Organization for Research and Treatment of Cancer) as a standardized European QOL instrument. The aim of this study was to evaluate the effect of radical procedures such as extensive lymph node resection and combined resection of adjacent organs on patients' QOL. From 1992 to 1996, 152 patients underwent total gastrectomy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…In the present study, there were no differences in quality of life relating to the extent of the lymphadenectomy, in agreement with the results of other studies 14,15 . Thybusch-Bernhardt et al 15 analysed a series of 152 patients with gastric cancer, 81 per cent of whom had undergone a D2 lymphadenectomy and 19 per cent an extended gastrectomy.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, there were no differences in quality of life relating to the extent of the lymphadenectomy, in agreement with the results of other studies 14,15 . Thybusch-Bernhardt et al 15 analysed a series of 152 patients with gastric cancer, 81 per cent of whom had undergone a D2 lymphadenectomy and 19 per cent an extended gastrectomy.…”
Section: Discussionsupporting
confidence: 94%
“…Thybusch-Bernhardt et al 15 analysed a series of 152 patients with gastric cancer, 81 per cent of whom had undergone a D2 lymphadenectomy and 19 per cent an extended gastrectomy. They concluded that neither operative procedure adversely affected the patient's state of health.…”
Section: Discussionmentioning
confidence: 99%
“…All patients in our study had undergone radical surgery before they commenced adjuvant treatment. Several research groups, using a variety of instruments [Short Form (SF-36) Health Survey, D15, Spitzer Quality of Life Index, eortc qlq-C30 and -STO22], have reported a reduction in qol in similar populations [18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies (Koster et al, 1987;Kusche et al, 1987;Buhl et al, 1990;Korenaga et al, 1992;Jentschura et al, 1997;Wu et al, 1997a;Zieren et al, 1998;Svedlund et al, 1999;Thybush-Bernhardt et al, 1999) of QOL after gastric cancer surgery provided important background for design of this study, delineating a number of specific hypotheses and research questions related to surgery and survivorship. This report examines QOL of gastric cancer patients receiving either D1 or D3 surgery.…”
mentioning
confidence: 99%